Literature Review on Football Learning Methods in Physical Education Curriculum - Ridwan, Andi; Bachtiar, Ishak (Sains Global Institut, Indonesia, 2025)
This study is a literature review of 18 articles discussing football learning methods in the physical education curriculum for the 2015–2025 period. The purpose of this study was to analyze the effectiveness of various learning approaches, including Teaching Games for Understanding (TGFU), Small-Sided Games (SSG), direct instruction, hybrid models, digital media, cooperative learning, and the scientific approach (5M). A systematic review method was used to select articles from various databases such as Google Scholar, Scopus, DOAJ, Sinta, and Garuda. Of the 125 initial articles, 18 met the inclusion criteria and were fully analyzed. The synthesis of results showed that game-based models were the most effective approach in improving students' tactical understanding and decision-making, with a 33–44% increase in tactical variables. Learning through 3v3 SSG consistently increased passing accuracy by 40.2%, while TGFU increased tactical awareness by 33.1%. In terms of basic technique, direct instruction provided significant improvements, such as a 12.8% increase in dribbling speed, a 40.4% increase in shooting accuracy, and a 31.3% increase in heading skills through video. The hybrid model proved to be the most comprehensive, with an average improvement of 43.9% in both technique and tactics. Digital media demonstrated additional effectiveness, with a 25–35% increase in technical skills. This study concluded that optimal football learning requires a combination of a game-based approach, systematic technique training, and the use of technology. The hybrid model is recommended as the most effective learning strategy for modern physical education curricula.